Les éco-spiritualités contemporaines (Seismo, 2024)
While since the 1960s, environmental degradation has been largely denounced on a global scale, this book considers that it is around 2015 that environmental mobilizations in Switzerland take a particular socio-cultural turn. The United Nations Climate Conference (COP21) meets in Paris, Pope Francis publishes the encyclical Laudato si' as a call to humanity to consider ecological issues, ecofeminist perspectives are widespread, and collapsologist theses resonate through media. This book presents the issues, analyses and results of six years of empirical research based on this turning point. It shows the significance of the cultural change it is bringing about in Switzerland, and particularly in the French-speaking part of the country. A process of “spiritualization of ecology” is identified and discussed in connection with an “ecologization of religion”. The research team, made up of sociologists and anthropologists, focused on participant observation of public ecological actions, as well as on interviews with a number of key actors involved in eco-spirituality.